1970
DOI: 10.1136/bmj.4.5728.157
|View full text |Cite
|
Sign up to set email alerts
|

Purpura fulminans treated with hyperbaric oxygen.

Abstract: Medical Memoranda MEDICALJOURNAL 157 direct pressure on the optic chiasma from a dilated third ventricle (Brain, 1962), the exact mechanism cannot be categorically stated. The exact mechanism of recovery also cannot be fully explained, though it is known that recovery of vision can follow prolonged blindness in children with hydrocephalus (Lorber, 1967). Shaffer and Hetherington (1969) suggested that the neuroglial framework is more susceptible than the neurones to an increase in surrounding pressure, and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…66 -70 Several researchers have reported success in reducing mortality and the amount of amputated limb tissue by HBO adjunctive to the intensive care treatment. [71][72][73] HBO therapy should be instituted as soon as possible to reduce the extent of necrosis. The rationale for HBO is similar to that described for the treatment of acute peripheral ischemia.…”
Section: Purpura Fulminansmentioning
confidence: 99%
“…66 -70 Several researchers have reported success in reducing mortality and the amount of amputated limb tissue by HBO adjunctive to the intensive care treatment. [71][72][73] HBO therapy should be instituted as soon as possible to reduce the extent of necrosis. The rationale for HBO is similar to that described for the treatment of acute peripheral ischemia.…”
Section: Purpura Fulminansmentioning
confidence: 99%
“…Treatment includes replacing fluids or blood, inotropes, oxygenation and mechanical ventilation, and support of multiorgan system failure in an individual, which was altogether absent in our case 10. In suspected patients, the role of timely and aggressive use of hyperbaric oxygen has been proven beneficial as it helps prevent ischaemic changes due to poor tissue reperfusion 11. The neonate in our case study was assumed to be suffering from a hereditary deficiency of protein C and S as it is the most common form of purpura fulminans (PF) in neonates 12.…”
Section: Global Health Problem Analysismentioning
confidence: 87%
“…In some studies treatment with hyperbaric oxygen has shown some benefit in PF cases. 22 However, in our study we treated only one with hyperbaric oxygen.…”
Section: Discussionmentioning
confidence: 98%